Sequential extraction and risk assessment of pollutants from one major tributary of the Ganga. Issue 3 (17th December 2021) - Kumar, Vinay; Sahu, Pokhraj; Markandeya,
Abstract: The geochemical fractionation of toxic heavy metals Cd, Pb, Cr, Co, Mn, Ni, Cu, Fe and Zn was investigated in 10 different sites of river bed sediments (up, mid and downstream) of Gomti River at Lucknow city. Sequential extraction technique was used to identify the distribution of trace elements binding in different fractions; i.e., exchangeable, carbonate, Fe and Mn oxide, organic matter and residual. Heavy metal concentrations were least at upstream and significantly higher in mid and downstream. Fractionation indicated that dominant metals were bound in residual fraction to the bed sediments except for Cd and Pb, which were bound in an equivalent fraction. Geo-accumulation index factor reveals that the enrichment of heavy metals in the bio-available fraction is contributed anthropogenically. Hierarchical cluster analysis also shows the metal pollution load in the river. Risk assessment code of Cd and Ni showed very high risk (ranged from 54.41 to 85.56 and 20.57 to 44.92 respectively) followed by Pb (high risk), Zn, Co (medium risk), Cr, Mn, Cu, Fe (low risk) in Gomti River water. Further, concentrations of Cd and Pb at mid Lucknow were 31 and 75%, high enough to pose a substantial risk to the environment. HIGHLIGHTS: The geochemical fractionations of toxic heavy metals were investigated. Sequential extraction technique was used to identify the distribution of trace metals binding in different fractions. Geo-accumulation index factor reveals that the enrichment of heavy metals in the bio-available fraction is contributed anthropogenically. Hierarchical cluster analysis also shows the metal pollution load in the river.